Simple organocatalytic route for the synthesis of starch esters - Tupa Valencia, Maribel Victoria (2013)
Starch acetates and starch butyrates with degree of substitution (DS) in the range of 0.06-1.54 were prepared by a simple direct solvent-free organocatalytic methodology of starch acylation. The starch esters synthesized have important applications in the food and pharmaceutical industries, among others. The acylation methodology used involves a non-toxic biobased α-hydroxycarboxylic acid as catalyst, and proceeds with high efficiency in absence of solvents. The effect of reaction time on the advance of starch modification was studied as a simple way to control the level of substitution achieved, when all other reaction parameters were kept constant. Starch esters were characterized by means of Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), thermogravimetric analysis (TGA) and X-ray diffraction (XRD). FTIR spectroscopy qualitatively confirmed the esterification of starch by the appearance of bands which are associated with esters groups. Scanning electron microscopy showed that the granular structure of the polysaccharide was preserved upon acylation, although acylated granules had rougher surfaces; and wrinkles, grooves and deformed zones appeared in some granules at high DS. Thermogravimetric analysis showed a gradual reduction in the water content of acylated starches, as well as noticeable changes in their thermal properties at increasing DS. X-ray diffraction analysis showed that the acetylation treatment led to lower crystallinity at increasing DS, although characteristic corn starch A-type patterns could be identified even at the highest DS achieved (DS = 1.23). Specific bands and weight losses derived from FTIR and TGA data could be very well correlated with the substitution degree achieved in acetylated starches at DS lower/equal than 0.6. The organocatalytic methodology described for the synthesis of starch acetates and butyrates has the potential to be easily extended to the synthesis of other starch esters using a variety of anhydrides or carboxylic acids as acylating agents.